Scanning and transmission electron microscopy of the histopathological impact of Macrogyrodactylus clarii (Monogenea: Gyrodactylidae) on the gills of catfish, Clarias gariepinus - El-Naggar, Mohammed Mohammed; Cable, Joanne; Zaky Arafa, Safaa; El-Abbassy, Samir Ahmed; Kearn, Graham C (Folia parasitologica, 2016)
Scanning and transmission electron microscopy (TEM) were used to study the histopathological effects of the monogenean Macrogyrodactylus clarii Gussev, 1961 on the gills of the catfish Clarias gariepinus (Burchell). Suction generated during attachment created 'footprints' on host surfaces in which the host tissues were elevated above the general gill surface. 'Footprints' were bordered by four clefts caused by the muscular flaps on the anterior, lateral and posterior margins of the haptor. The hamuli points penetrate the gill tissue but no evidence was found for the insertion of the marginal hooklets. At the site of attachment, host cells adjacent to the lateral flaps often appeared compressed and widely spaced with large intercellular spaces. Desquamation of these surface epithelia was also apparent and some of the widely spaced epithelial cells had pseudopodium-like processes. Cells within the upper surface epithelial layer of the host were vacuolated and necrotic. Ruptured blood capillaries (blood spaces) in the secondary gill lamellae contained atypical compressed erythrocytes, agranular and granular leucocytes and evidence of haemorrhaging. Cells with fibrotic cytoplasm, putative phagocytes and host mucous cells were evidence of a host response at the site of parasite attachment. The possible role of these cells is discussed in relation to host resistance against infection.
Keywords: Animals; Microscopy, Electron, Transmission; Trematoda; Gills; monogeneans; infekce červy třídy Trematoda; Trematode Infections; Microscopy, Electron, Scanning; nemoci ryb; mikroskopie elektronová rastrovací; fish disease; Fish Diseases; žábry; ultrastructure; sumci; aquatic health; transmisní elektronová mikroskopie; zvířata; histopathology; Catfishes